The use of experiential learning as a teaching strategy in Life Sciences. - McPherson-Geyser, G.; De Villiers, R.; Kavai, P. (My University, 2020)
The implementation of experiential learning within schools may hold many advantages. The objective of this study was to identify how experiential learning influences the teaching and learning of Life Sciences (biology). This qualitative inductive research focused on creating a rich amount of data through a multiple case study approach. The collection and analysis of data were done through the use of interviews, classroom observations and worksheet checklists. The interpretivist researcher in this study chose dual-medium public high schools of different socialeconomic backgrounds to participate in this study. Life Sciences teachers in Johannesburg, Gauteng, South Africa were interviewed and observed in their classes while teaching. This study showed that teachers do not fully understand the context of experiential learning. The issue that was addressed was the need for quality education by enforcing the correct use of experiential learning. The insertion of generic skills in schools will improve the development of Life Sciences learners and enable them to subsequently progress in the classroom. An experience not utilized in another area of education has not value, specifically in the Life Sciences classroom. This experience permitted learners to form a union between the outside of the classroom and the theory taught inside the classroom when testing implications. These implications can form part of experiments, subject matter or any theme related to science and society. Experiential learning sustained a gateway to the learners’ outside lives, where the concepts came alive in common areas of their daily lives. Keywords: biology, experiential learning, life sciences, teachers, teaching strategy